Challenges in personal and clinical dosimetry using Li2B4O7 and MgB4O7 as TLD and OSLD - Leo Sousa Santiago de Oliveira; Luiza Freire de Souza; Gabriela Guimarães Donald; Malu Fernandes Serra D’Emidio; Andréa de Lima Ferreira Novais; Divanízia Souza (Brazilian Journal of Radiation Sciences)
Thermoluminescent (TLD) and optically stimulated luminescent dosimeters (OSLD) are essential in radiation dosimetry. Such dosimeters can be easily transported due to their small size and can be used in in vivo dosimetry and anthropomorphic simulations. In this work, the dosimetric properties of Li2B4O7 and MgB4O7 compounds were evaluated based on their response to the applied stimulus, whether thermal or optical. The linear dose response range of the luminescent signal, its fading, the lowest detectable dose, and reproducibility are important parameters in determining a good dosimeter for clinical and personal dosimetry. Therefore, the objective of this work was, based on studies performed by other authors on dosimetric characterizations of doped a codoped Li2B4O7 and MgB4O7, to point out those compounds with the greatest potential for applications in personal and clinical dosimetry using TL and OSL techniques. Considering the results described in other works, the materials that stood out for use in personal and clinical dosimetry were Li2B4O7:Cu and MgB4O7:Dy,Na. In several of the reported studies, no data related to LDD, fading and reproducibility of the luminescent signal of the investigated compounds were found. Therefore, there are many possibilities for investigations into these two types of compounds for the purpose of their use in personal and clinical dosimetry. Further studies will provide a broader scientific basis for choosing appropriate dosimetric materials for these applications.